The Impacts of Lifestyle Modification Education towards Cardiovascular Risk Profile - Fonny Cokro; Abdul Rahem; Lisa Aditama; Franciscus C. Kristianto (Universitas Padjadjaran, 2018)
Obesity is one of the risk factors of cardiovascular disease. The prevalence of obesity in Indonesia has increased in the last few years, therefore some efforts to reduce the risk is needed. In the current study, efforts are given through 3-week lifestyle modification education, with 3-month total of follow-up (from March to June 2014) and then the impacts on cardiovascular risk profile were observed and seen on 24 sedentary male workers in University of Surabaya with obese II. This study used before-after study design in order to see the impacts of the 3-week lifestyle modification education towards change of knowledge, dietary behavior, body mass index (BMI), waist circumference, and cardiovascular risk profile through various educational methods (face-to-face session, given recorder of face-to-face session, and combination of both methods). Statistical analysis was performed using Wilcoxon signed test. Result showed an increasing knowledge in face-to-face group (p=0.046). However, there were no significant changes in other variables (dietary behavior based on healthy diet indicator (HDI), BMI, waist circumference, and also cardiovascular risk profile) in all groups between before and after education intervention (p>0.05). In conclusion, lifestyle modification education given for 3 weeks did not reduce the cardiovascular risk profile on sedentary male workers with obese II. Longer term intervention and multicomponent program including behavior therapy may be needed to succeed lifestyle changes and reduce cardiovascular risk.Keywords: Behaviour, cardiovascular risk, education, knowledge, lifestyle modification Pengaruh Edukasi Gaya Hidup terhadap Perubahan Risiko Penyakit KardiovaskularAbstrakObesitas merupakan salah satu faktor risiko penyakit kardiovaskular. Prevalensi obesitas di Indonesia mengalami peningkatan beberapa tahun terakhir, sehingga diperlukan upaya untuk menguranginya. Pada penelitian ini, upaya dilakukan melalui pemberian edukasi gaya hidup yang dilakukan selama 3 minggu, dengan total follow-up sampai dengan 3 bulan dari bulan Maret hingga Juni 2014, kemudian dilihat dan diamati ada atau tidaknya penurunan risiko penyakit kardiovaskular pada 24 orang karyawan pria obese II di Universitas Surabaya. Penelitian ini memiliki rancangan before-after study design untuk menguji pengaruh edukasi gaya hidup yang diberikan selama 3 minggu terhadap variabel pengetahuan, perubahan perilaku, body mass index (BMI), lingkar perut, dan risiko penyakit kardiovaskular melalui berbagai metode pemberian edukasi (tatap muka, rekaman/recorder, dan kombinasi). Analisis dengan Wilcoxon signed test menunjukkan bahwa terdapat peningkatan pengetahuan hanya pada subgrup tatap muka (p=0,046). Tidak terdapat perubahan yang signifikan terhadap variabel lainnya (perubahan perilaku berdasarkan healthy diet indicator (HDI), BMI dan lingkar perut, serta risiko penyakit kardiovaskular) pada semua subgrup antara sebelum dan sesudah edukasi (p>0,05). Edukasi gaya hidup yang diberikan selama tiga minggu tidak memberikan penurunan risiko penyakit kardiovaskular pada karyawan pria obese II. Dibutuhkan intervensi jangka panjang dan program multikomponen yang memuat terapi perilaku untuk menyukseskan perubahan perilaku dan menurunkan risiko kardiovaskular.Kata kunci: Edukasi, gaya hidup, pengetahuan, perilaku, risiko kardiovaskular